Legal innovations for balancing environmental protection and public health in urban polluted areas - Jinglin Zhao; Ruolin Zhang (Frontiers in Public Health)
IntroductionBalancing environmental protection with public health in urban polluted areas presents significant governance and legal challenges. Traditional regulatory approaches often operate in silos, failing to integrate environmental sustainability with health policies, leading to inefficiencies and inequitable outcomes.MethodsThis study introduces the Resilient Ecosystem Management Framework (REMF), an interdisciplinary approach that combines legal innovations, adaptive governance mechanisms, and data-driven environmental health strategies. It critically analyzes the limitations of existing legal frameworks in addressing urban pollution and associated health risks. REMF is developed by integrating adaptive legal instruments, participatory governance, and real-time environmental monitoring. Case studies and quantitative modeling are applied to evaluate the framework's effectiveness in urban environments.ResultsThe findings demonstrate that REMF enhances policy coordination, enables more effective regulatory enforcement, and improves environmental and health outcomes by leveraging legal adaptability and technological advancements. Real-time environmental data and predictive analytics allow for dynamic adjustments to legal thresholds, ensuring responsive and equitable governance.DiscussionMoreover, the framework facilitates active stakeholder engagement, ensuring that vulnerable populations benefit from pollution mitigation efforts. This research provides a scalable and replicable legal model that aligns environmental law with public health imperatives, offering practical insights for policymakers, urban planners, and environmental regulators. By demonstrating how legal frameworks can evolve to address contemporary urban challenges, this study contributes to the broader discourse on sustainable urban governance and environmental justice.